2013
DOI: 10.1186/1471-2202-14-77
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prenatal and early postnatal tocotrienol-rich fraction supplementation on cognitive function development in male offspring rats

Abstract: BackgroundRecent findings suggest that the intake of specific nutrients during the critical period in early life influence cognitive and behavioural development profoundly. Antioxidants such as vitamin E have been postulated to be pivotal in this process, as vitamin E is able to protect the growing brain from oxidative stress. Currently tocotrienols are gaining much attention due to their potent antioxidant and neuroprotective properties. It is thus compelling to look at the effects of prenatal and early postn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
3
9
0
Order By: Relevance
“…Increased expression of these proteins may enhance synaptic transmission leading to cognitive improvement because tocotrienol uptake in fetal brain has been reported to be high and it promoted long lasting learning ability by influencing the brain development [31]. Based on our results, it can be concluded that TRF treatment increases the expression of proteins involved in synaptic function.…”
Section: Discussionsupporting
confidence: 52%
“…Increased expression of these proteins may enhance synaptic transmission leading to cognitive improvement because tocotrienol uptake in fetal brain has been reported to be high and it promoted long lasting learning ability by influencing the brain development [31]. Based on our results, it can be concluded that TRF treatment increases the expression of proteins involved in synaptic function.…”
Section: Discussionsupporting
confidence: 52%
“…Although able to acquire the task at the end of training, treated rats needed longer to develop a precise spatial preference for the goal, showing longer escape latency and path length respect to non-supplemented controls; in addition, they spent less time swimming in the goal quadrant after platform removal [79]. It is worth mentioning that spatial cognitive performance on MWM was found increased, instead of impaired, in adult offspring from dams supplemented through pregnancy and lactation with tocotrienol-rich fraction (providing 300 and 700 mg/kg of total tocopherols and tocotrienols, respectively), with better escape latency and shorter distance travelled after the third day of training, and increased memory retention at the probe test [102]. We think that such conflicting data is possibly due to different experimental study design by Nagapan et al [102], since high doses of tocotrienols were used for supplementing dams, and supplementation was continued in offspring until they were tested, at 16 weeks postnatal.…”
Section: α-Tocopherol and Brain Developmentmentioning
confidence: 99%
“…On the other hand, because of their unsaturated side chain, penetration into brain tissues is easier for TT [8]. Hence, oral supplementation of TT could be effective in protection of the brain against oxidative stress.…”
Section: Introductionmentioning
confidence: 99%